2009
DOI: 10.1259/bjr/25645894
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid SPECT–CT and PET–CT imaging of differentiated thyroid carcinoma

Abstract: Hybrid imaging modalities such as radioiodine single photon emission CT with integrated CT ((131)I SPECT-CT) and 2-(fluorine-18)-fluoro-2-deoxy-D-glucose positron emission tomography with integrated CT (FDG PET-CT) allow the rapid and efficient fusion of functional and anatomic images, and provide diagnostic information that may influence management decisions in patients with differentiated thyroid carcinoma (DTC). Diagnostic localisation and therapy of these tumours are dependent upon their capacity to concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 17 publications
1
28
0
1
Order By: Relevance
“…SPECT/CT is an excellent diagnostic tool for rapid evaluation of suspected physiologic mimics and can accurately localize radioiodine distribution to salivary glands, dental fillings, retrosternal goiter, esophageal or airway secretions, hiatal hernias, bowel diverticula, breast, skin contamination, and benign uptake related to radioiodine retention in cysts, bronchiectasis, thymus, benign struma ovarii, or menstruating uterus (53)(54)(55)(56)(57)(58)(59). Several reports outline the usefulness of SPECT/CT for solving difficult diagnostic interpretations and revealing unusual metastatic lesions in the liver, kidney, central nervous system, erector spinae muscle, and rectus abdominis muscle (60)(61)(62)(63)(64).…”
Section: Utility Of Spect/ct For Problem Solving (Evaluation Of Unusumentioning
confidence: 99%
“…SPECT/CT is an excellent diagnostic tool for rapid evaluation of suspected physiologic mimics and can accurately localize radioiodine distribution to salivary glands, dental fillings, retrosternal goiter, esophageal or airway secretions, hiatal hernias, bowel diverticula, breast, skin contamination, and benign uptake related to radioiodine retention in cysts, bronchiectasis, thymus, benign struma ovarii, or menstruating uterus (53)(54)(55)(56)(57)(58)(59). Several reports outline the usefulness of SPECT/CT for solving difficult diagnostic interpretations and revealing unusual metastatic lesions in the liver, kidney, central nervous system, erector spinae muscle, and rectus abdominis muscle (60)(61)(62)(63)(64).…”
Section: Utility Of Spect/ct For Problem Solving (Evaluation Of Unusumentioning
confidence: 99%
“…SPET-CT further characterized 21 out of 52 (40 %) foci of I-131 uptake, differentiating metastases from benign, physiological mimics of disease [28]. In a similar fashion, diagnostic I-131 SPET-CT performed before thyroid remnant ablation accurately characterized central neck and distant distributions of I-131 activity, correctly classifying equivocal planar imaging findings as benign or malignant [22,23]. The incremental value of SPET-CT over planar imaging was reported in 53 out of 130 (41 %) foci, with confident identification of thyroglossal duct and thyroid bed remnants [22,23].…”
Section: Spet-ct Diagnostic Interpretationmentioning
confidence: 78%
“…In a similar fashion, diagnostic I-131 SPET-CT performed before thyroid remnant ablation accurately characterized central neck and distant distributions of I-131 activity, correctly classifying equivocal planar imaging findings as benign or malignant [22,23]. The incremental value of SPET-CT over planar imaging was reported in 53 out of 130 (41 %) foci, with confident identification of thyroglossal duct and thyroid bed remnants [22,23]. Others have confirmed that indeterminate neck lesions on planar scans, when restudied with SPET-CT, can be re-classified as thyroid remnants, lymph node metastases (Fig.…”
Section: Spet-ct Diagnostic Interpretationmentioning
confidence: 87%
See 2 more Smart Citations